The Thought of the Ulama of the Islamic Association on the Transformation of the Social and Cultural Role of Women as Housewives: Implications for the Concept of Gender Equality - Beni Ahmad Saebani; Mustopa (Faculty of Law, Universitas Pekalongan, 2025)
The Unity of Islam cleric's thinking is distinctive in determining legal provisions, especially in formal rituals. However, a different approach is used when discussing the shift in the role of housewives, which does not yet have a firm view from Islamic Unity scholars. This research uses descriptive analysis method by collecting data through observation, interviews, and documentation, as well as the main data source from the opinions of Islamic Unity scholars. The aim is to analyze the thoughts of Islamic Unity scholars on the changing social and economic roles of women as housewives. The results of the study were analyzed using an empirical juridical approach, gender equality theory, and the concept of family law reform from Tahir Mahmood. In conclusion, the Islamic Union scholars consider the role of women in family law as part of muamalah that can be developed progressively, while still paying attention to the principles of Islamic law. This thinking is socialized positively through various activities to the community, with the al-maslahah al-mursalah approach to maintain the principle of women's dual role as housewives, without equating all activities between men and women.